Abrasive wear response of TIG-melted TiC composite coating: Taguchi approach - Maleque, Md. Abdul; Bello, K A; Adebisi, A A; Dube, A (IOP Publishing, 2017)
In this study, Taguchi design of experiment approach has been applied to assess wear behaviour of TiC composite coatings deposited on AISI 4340 steel substrates by novel powder preplacement and TIG torch melting processes. To study the abrasive wear behaviour of these coatings against alumina ball at 600o C, a Taguchi’s orthogonal array is used to acquire the wear test data for determining optimal parameters that lead to the minimization of wear rate. Composite coatings are developed based on Taguchi’s L-16 orthogonal array experiment with three process parameters (welding current, welding speed, welding voltage and shielding gas flow rate) at four levels. In this technique, mean response and signal-to-noise ratio are used to evaluate the influence of the TIG process parameters on the wear rate performance of the composite coated surfaces. The results reveal that welding voltage is the most significant control parameter for minimizing wear rate while the current presents the least contribution to the wear rate reduction. The study also shows the best optimal condition has been arrived at A3 (90 A), B4 (2.5 mm/s), C3 (30 V) and D3 (20 L/min), which gives minimum wear rate in TiC embedded coatings. Finally, a confirmatory experiment has been conducted to verify the optimized result and shows that the error between the predicted values and the experimental observation at the optimal condition lies within the limit of 4.7 %. Thus, the validity of the optimum condition for the coatings is established.